2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6945071
|View full text |Cite
|
Sign up to set email alerts
|

Empowering patients to perform physical therapy at home

Abstract: In this paper we address the problem of patient adherence to physical therapy using a sensor-enabled virtual reality gaming interface that motivates users to complete their exercises while collecting quantitative data. The system also allows the therapist to monitor and interact with patients remotely providing reinforcing feedback and support with the CollaboRhythm care delivery platform. The data collected with this system enables the therapist and the patient to make informed decisions about patient treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Only two included studies [ 28 , 29 ] used VR as a part of home rehabilitation for patients after TKA. Gonzalez-Franco et al [ 75 ] tested the rehabilitation protocol for patients after TKA in a group of healthy volunteers as a part of home rehabilitation using modern technology. Participants emphasize the possibility of intuitive and accessible teaching of the correct performance of exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Only two included studies [ 28 , 29 ] used VR as a part of home rehabilitation for patients after TKA. Gonzalez-Franco et al [ 75 ] tested the rehabilitation protocol for patients after TKA in a group of healthy volunteers as a part of home rehabilitation using modern technology. Participants emphasize the possibility of intuitive and accessible teaching of the correct performance of exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation is another possible application for PoMLab. Recent studies have attempted to perform rehabilitation at home, especially through the use of tablet devices, tablet games, or other devices that can connect to the tablet through Bluetooth [ 24 , 25 ]. We need to investigate whether our PoMLab application is effective for home-based rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…With "Use-Dependent Adaptation", a Kinect device was often used to give visual tailored feedback about the performance or remaining time the end-user had [55][56][57][58][59][60][61] and/or by tailoring the difficulty of the tasks to end-user input, like performance [52][53][54]. In "User Controlled Customization", end-users tailored avatars that could represent an idealized self or actual self [7,44,49,51,49] and others defined the objectives, difficulty level or specified the stimuli of a product [45,47,48,50].…”
Section: Tailoringmentioning
confidence: 99%
“…For example, two studies suggested that the users had positive subjective experiences while playing the game (e.g., enjoyment and a sense of accomplishment) and that they were motivated by the tailoring aspect of the activity [53,59]. Regarding physical health, the physical performance improved significantly [60], which was a significant [52] or a percentage improvement in motor and sensory impairments [56]. End-users that participated in both conditions rated the experimental game as more enjoyable [55], and after playing an imitative collaborative game with a robot, children with ASD played more with each other [58].…”
Section: Valid Andreliable Measurementsmentioning
confidence: 99%